Clinical course and surgical outcomes in middle-age adults with anomalous aortic origin of a coronary artery. (20th July 2021) - Javaid, A; Sehgal, S; Khetarpal, BK; Singh, A; Diep, J; Ahsan, C; Malhotra, S
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Patients with anomalous aortic origin of a coronary artery (AAOCA) present with a wide range of clinical manifestations, including ischemic symptoms (chest pain or dyspnea) and sudden cardiac death (SCD). Studies have identified coronary anatomic characteristics associated with a higher risk of SCD. However, most of the published literature consists of studies in adolescents and young adults. There is a paucity of data regarding outcomes in middle-aged patients. Current guidelines reveal gaps in evidence for identification of adults are at risk for SCD, and for whom surgery is beneficial. Purpose: To study the clinical course and rate of major adverse cardiac events (MACE) in middle-aged adults with AAOCA based on presenting symptoms, coronary anatomy on coronary computed tomography angiography (CCTA), stress test results, and surgical management. Methods: We included all patients from January 2013 to December 2019 age > 18 at our institution who were found to have AAOCA.  Patients with the following were excluded to minimize confounding factors which could cause MACE: coronary artery disease (CAD) with >50% stenosis in any coronary vessel, CAD requiring revascularization, heart failure with ejection fraction <40%, history of heart transplant, and non-AAOCA congenital heart disease. All patient charts were reviewed for demographics, coronary anatomy on CCTA, presenting symptoms, rationale for pursuing stress testing and CCTA, nature of surgical interventions, post-surgical course, and MACE (cardiovascular death, myocardial infarction, and need for coronary revascularization). All patients underwent PET as well as treadmill stress testing. Results: Of 19, 367 patients who underwent CCTA, 47 met inclusion criteria, with median age at diagnosis of 54 and median follow-up of 48 months. No patients suffered MACE. Twenty-five patients had AAORCA and 22 had AAOLCA (Table 1). Ten patients with AAORCA and 8 patients with AAOLCA presented with ischemic symptoms and had coronary anatomy characteristics associated with higher risk of SCD, as well as ischemia corresponding to the anomalous artery on stress testing and did not undergo surgery due to personal preference. Five symptomatic patients with stress-induced ischemia corresponding to the anomalous artery underwent surgery and all achieved symptom relief over a median follow up of 5 years. Conclusion: As AAOCA is a significant cause of SCD in young adults, it is compelling to observe this adult cohort in which no patients experienced MACE, including 18 symptomatic patients with high-risk anatomy and stress-induced ischemia, as well as a Class I recommendations for surgery.  The results suggest that although surgery may be beneficial for symptom relief, it does not necessarily improve mortality over an intermediate follow-up period.  Future studies should examine surgical outcomes in middle-aged cohorts with larger sample sizes.